Taking Charge in Time of Crisis: A Multi-Sites Case Study of School Leaders in Kedah, Malaysia - Othman, Saiful (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2024)
The resolution of a crisis necessitates the implementation of efficient problem-solving strategies and the ability to make effective decisions. The occurrence of a crisis in schools presented various risks to the well-being of teachers, staff, and students, as well as the overall objectives, vision, and mission of the schools. Consequently, school leaders were confronted with significant challenges in addressing these issues while maintaining students' academic performance and minimising overall disruptions in education. This study aimed to examine the strategies and approaches employed by school leaders for effective problem-solving and decision-making in times of crisis. The objective was achieved by employing a qualitative research design. This study involved conducting semi-structured interviews with six school leaders from government secondary schools under the jurisdiction of the Ministry of Education (MOE). The selected schools were from three district education offices (PPD) located in Kedah. This study provided a valuable lesson for educators, policymakers, and other related stakeholders on how to deal with crises in the future.